KONVERGENSI SIMBOLIK DALAM KOMUNIKASI KELOMPOK KOMUNITAS STAND UP INDO PEKANBARU - Elsakina, Raissa F.; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The members of Stand Up Indo Pekanbaru community keep their solidarity well maintained in their interaction, so the community is able to survive and to exist up to this day. The interaction can be done via social media, and also when they gather together. The community arrange weekly activities such as open mic and sharing comedy. Long term interaction resulting in communication understanding which only the community can relate to, which is known as symbolic convergence. This research is aimed to identify the process of fantasy theme formation, the process of symbolic cue formation, as well as the form of fantasy chain in the group communication of Stand Up Indo Pekanbaru community members.This research uses qualitative research method, with symbolic interaction approach. The technique used in informant selecting is snowball technique, with the informants are three in numbers. The techniques used in data gathering are participant observation, in-depth interview, and documentation. The techniques used in data validity examination are data extension technique and triangulation technique.This research shows that first, the process of fantasy theme formation is originated from symbolic interaction which leading to symbolic convergence, and then the message dramatization process happens. The dramatized message triggers the form of fantasy series, which produces fantasy theme in group. Second, the symbolic cue formed in the community is adopted, which means that the symbolic cue has been used before. Third, the fantasy chain form of ‘Lord Tengku’ fantasy theme resulted in three times joke-toned fantasy attempts by its participants. ‘Penampilan comic’ fantasy theme resulted in two times fantasty attempt by imagining a certain event, which is event in the past and event in the future.Keyword : symbolic convergence , fantasy theme, fantasy chain, symbolic cue